REKA BENTUK MODEL PENGAJARAN TARANUM AL-QURAN: ANALISIS TERHADAP MODEL-MODEL PENGAJARAN YANG TERPILIH: Taranum al-Quran Teaching Model Design: Analysis of Selected Teaching Models - Mohamad Salleh, Muhamad Nasir; Hussin, Zaharah; Mohamed, Mohd Faisal (Journal of Islamic Educational Research, 2020)
The design of Taranum al-Quran Teaching Model for Higher Education Institutions (MPTQ-IPT) requires a clear, orderly and effective modeling framework. Therefore, the objective of this study is to analyze the selected teaching models as a conceptual framework for the formation of MPTQ-IPT. In this study, the researcher has identified three suitable and appropriate teaching models, namely the Quran Teaching Model according to al-Qabisi, Basic Teaching Model according to Robert Glaser and the support of Taranum Teaching Model according to Mazhair Shahroz Muhasip. The unique result of the combination of all three teaching models produces the six main components of taranum teaching. Overall, the formation of MPTQ-IPT through research on the models presented is an effort to ensure the process through systematic research, debate and evaluation procedures to transform the teaching pedagogy of taranum lecturers from time to time.